El Arbitraje Administrativo en la contratación pública peruana: ¿evolución o contradicción? - Tafur Scaglia, Sergio Alberto (2021)
Due to modern times, many commercial relations have emerged and have led society to new types of conflict that require to be analyzed with particular attention. This context has shown that the ordinary instances of law do not have the necessary knowledge to face this type of conflicts. Thereby, modern law, as a social phenomenon, has adapted to this evolution. This is where arbitration has progressively become more relevant over the years. Because traditional legal branches, such as the Judiciary system, are not efficient enough to resolve disputes in their jurisdiction. By virtue of this, the Peruvian State, within its legal framework, has established the figure of arbitration as a means of bypassing national judicial courts in order to settle governmental and private entity disputes. To such an extent that the government itself in its PublicProcurement Act of 2008 —published through Legislative Decree 1017— mentioned the concept of “administrative arbitration”, which is still used today without having a clear and precise definition. The purpose of this article is to develop this figure based on the reason for its creation and to analyze whether this figure finds a reason to exist in the current context of public procurement or if it constitutes a legal chimera still in the making. Therefore, our intention in the following lines, without being exhaustive, is to give a brief reflection on the importance of administrative arbitration regulation regarding the concept of arbitration and to analyze if this figure already exists in the current Peruvian framework or, on the contrary, if we are before the bureaucratization of the institution.